FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA MENURUT BB/U - Pribadi, Puspita Sari; Aristina, Nur Eva; Sianipar, Kandace (Ensiklopedia of Journal, 2025)
Abstract: Underweight nutrition in children under five is now a serious global problem, especially in poor and developing countries. The prevalence of underweight reached 29.5%. This figure places NTT as one of the provinces with the highest level of malnutrition in Indonesia. The purpose of the study was to determine the factors associated with the nutritional status of toddlers according to BB/U. The research design used in this study was Cross Sectional. The research was conducted in the Busalangga Health Center work area in August 2023. The study population was all toddlers in the Busalangga Health Center work area which amounted to 976 toddlers. The sample amounted to 293 toddlers. The sampling technique used Stratified Random Sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed an association between age at first pregnancy (p value: 0.003) and LBW (p value: 0.000) on the incidence of undernutrition. It is recommended that health centers improve malnutrition prevention programs that focus not only on mothers and toddlers but also on adolescents in order to prevent the incidence of stunting and malnutrition early on and empower posyandu cadres by increasing their knowledge and skills.Keywords: Toddler, Undernutrition, Age at first pregnancy.